Beyond Grammar and Vocabulary: A Literature Review on Higher-Order Thinking in EFL Writing Development - Az Zahra, Olivia; Wijayatiningsih, Testiana Deni (LPPM Universitas Pancasakti Tegal, 2024)
Developing EFL learners’ writing competence requires more than mastering grammar and vocabulary. Recent scholarship highlights the need to integrate higher-order thinking skills (HOTS) such as analysis, evaluation, and creativity to enable learners to construct meaning, respond critically to texts, and express original ideas in written form. This literature review synthesizes empirical and theoretical studies published over the last decade to examine how HOTS contribute to EFL writing development and how instructional practices can effectively foster them. Following a literature review methodology, studies were collected, analyzed, and categorized based on key themes: cognitive processes in EFL writing, pedagogical frameworks that promote HOTS, and challenges in integrating higher-order skills in classroom contexts. The findings show that HOTS-oriented instruction through approaches such as task-based learning, problem-based learning, and genre-based pedagogy significantly enhances learners’ ability to generate ideas, organize arguments, and reflect critically on their writing. However, research also reveals constraints, including teachers’ limited expertise, exam-oriented cultures, insufficient scaffolding, and learners’ low self-regulation. This review concludes that embedding HOTS within writing instruction is essential for preparing EFL learners to meet academic and real-world communication demands. It also underscores the importance of developing teachers’ pedagogical knowledge and designing learning environments that balance linguistic accuracy with critical thinking development.